2002
DOI: 10.1053/jhep.2002.33713
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity an independent risk factor for hepatocellular carcinoma in cirrhosis?

Abstract: Recently, several epidemiologic observations have suggested that obesity might be an independent risk factor for certain malignancies such as breast cancer, colon cancer, renal cell carcinoma, and esophageal adenocarcinoma. However, there are no studies examining the risk of hepatocellular carcinoma (HCC) in obesity. The aim of the present study was to determine whether obesity is an independent risk factor for HCC in patients with cirrhosis. Explanted liver specimens from a national database on patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
212
3
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(226 citation statements)
references
References 33 publications
6
212
3
5
Order By: Relevance
“…We identified 11 eligible cohort studies (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006), of which 7 on overweight (with a total of 5037 cases) (Calle et al, 2003;Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006;Samanic et al, 2006) and 10 on obesity (with a total of 6042 cases) (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006) were suitable for metaanalysis. Characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 11 eligible cohort studies (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006), of which 7 on overweight (with a total of 5037 cases) (Calle et al, 2003;Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006;Samanic et al, 2006) and 10 on obesity (with a total of 6042 cases) (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006) were suitable for metaanalysis. Characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were based on standardized incidence ratio (Møller et al, 1994;Wolk et al, 2001). Two studies consisted of patients with cirrhosis (Nair et al, 2002;N'Kontchou et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 90 % of people with obesity have fatty liver disease, including NASH and cirrhosis ( 16 ). One study of over 19,000 patients found that the incidence of HCC was higher in obese (defi ned as BMI > 30 kg / m 2 ) patients than in nonobese patients (4.0 % vs. 3.0 % , respectively; P = 0.013), and that obesity was associated with a 65 % increased risk of developing HCC ( 13 ). Another large prospective cohort study of more than 900,000 individuals reported that the mortality rate from liver cancer was fi ve times greater among those with a BMI between 35 -40 compared with those with a normal BMI ( 5 ).…”
Section: Th E Incidence Of Hepatocellular Carcinoma (Hcc) In the Unitedmentioning
confidence: 99%
“…Thus, initiation causes a change in the growth-regulatory network that becomes evident after the first replication cylce of GSTp þ cells. Treatment with tumour promoters, such as the progestin cyproterone acetate (CPA), or increased food intake further increases cell replication in preneoplasia, which is analogous to human hepatocarcinogenesis driven by anabolic steroids or overnutrition (Schulte-Hermann et al, 1990;Grasl-Kraupp et al, 1994;Fiel et al, 1996;Nair et al, 2002). This enhanced sensitivity of liver preneoplasia towards the various growth stimuli could result from an altered uptake, production and/or processing of endogeneous growth regulatory factors by the premalignant cell compartment.…”
mentioning
confidence: 99%